2020
DOI: 10.1155/2020/8877577
|View full text |Cite
|
Sign up to set email alerts
|

Bmi1 Severs as a Potential Tumor-Initiating Cell Marker and Therapeutic Target in Esophageal Squamous Cell Carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is a frequent malignant tumor with low 5-year overall survival. Targeting ESCC tumor-initiating cells (TICs) may provide a new research avenue to achieve better therapeutic effects of ESCC. However, the identity and characteristics of ESCC TICs remain poorly understood. Through genetic lineage tracing approach, we found that a group of Moloney murine leukemia virus insertion site 1- (Bmi1-) expressing cell populations present in the invasive front of the esophageal epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…As previously described, mice were treated with 50 µg/ mL 4NQO (Sigma, N8141) to induce ESCC formation. 36 Briefly, 6-week-old male mice were orally administered with 4NQO dissolved in drinking water for 16 weeks to induce the formation and development of ESCC. Subsequently, the mice were returned to normal water for 10 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described, mice were treated with 50 µg/ mL 4NQO (Sigma, N8141) to induce ESCC formation. 36 Briefly, 6-week-old male mice were orally administered with 4NQO dissolved in drinking water for 16 weeks to induce the formation and development of ESCC. Subsequently, the mice were returned to normal water for 10 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…To quantify the IHC staining results on patients with ESCC, the IHC staining intensity was assigned scores: 0 (negative), 1 (weak), 2 (medium), or 3 (strong), and IHC score was calculated by multiplying the percentage of positive cells (P) by the intensity (I), using the formula: Q=P×I; with a maximum score of 300. 36 The IHC score was calculated based on the percentage of positive cells within ESCC mouse model.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…IHC and H&E staining procedure had been described previously 38 . All the primary antibodies including METTL13 (GeneTex, GTX120626-S), Snail (Cell Signaling Technology, 3879T), and Ki67 (Affinity, AF0198) were used at dilution in 1:100.…”
Section: Methodsmentioning
confidence: 99%
“…At the molecular level, multiple studies have demonstrated that BMI1 can collaborate with the PRC2 protein EZH2, a well-known histone methyltransferase, to suppress gene transcription, likely through the enhancement of trimethylation of H3 at lysine 27 (H3K27me3) 16 18 . This epigenetic modification has been shown to play a crucial role in the regulation of self-renewal in both normal stem cells and TICs, also referred to as cancer stem cells 13 , 19 . Indeed, Chen et al showed that BMI1 high TIC promoted tumor invasive growth and lymph node metastasis in squamous cell carcinoma 14 .…”
Section: Introductionmentioning
confidence: 99%